Penerapan Etika Bisnis Islam Pada Rumah Jahit Zhuraida Di Desa Berembang Kecamatan Sekernan Kabupaten Muaro Jambi - Putri Adelia; Ambok Pangiuk; M. Maulana Hamzah (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This thesis is entitled Application of Islamic Business Ethics at the Zhuraida Sewing House in Berembang Village, Sekernan District, Muaro Jambi Regency. This research aims to determine the application of Islamic business ethics in accordance with the characteristics of the Prophet Muhammad according to M. Syafi'i Antonio and the indicators of Islamic business ethics are shiddiq, amanah, tabligh and fathanah. The method used in this research is descriptive qualitative, where in collecting data the researcher uses observation, interviews and documentation methods. The research results show that the Zhuraida Sewing House has implemented Islamic business ethics as exemplified by the Prophet and its characteristics, namely shiddiq (being honest) which is reflected in not doubling the price of the product, recognizing the weaknesses and strengths of the product. The nature of fathanah (intelligent) is reflected in the spiritual condition of owners and employees who continue to prioritize spirituality towards Allah SWT. and the Zhuraida Sewing House has implemented promotions through brochures and social media such as Whatsapp, Instagram, Facebook, Tiktok and others. However, there are still several obstacles that prevent the Prophet's qualities from being implemented, namely the nature of trustworthiness (keeping promises) which is caused by a lack of workers in the production department because the Zhuraida Sewing House is still neglecting its responsibilities in terms of taking time to complete the product. Then the tabligh (communicative) nature, namely online services, is not running well due to the lack of employees in the service admin section.